Simulações do clima para holoceno-médio usando modelo ETA - Marchi, Adriano Correia de (2013)
Climate variability and change are simulated during the Mid-Holocene (MH) for South America (SA), using the atmospheric general circulation model (AGCM) from the Center for Weather Forecasts and Climate Studies (CPTEC) with a T062L28 resolution and downscaling with the Eta model (at 20km resolution). Simulations were made by modifying the orbital parameters (Milankovitch cycles), adding a new parameterization (Berger, 1978) for typical values of the present and MH. Used the downscaling model with Eta for the present climate and the MH, resulting in two simulations (Eta 0k e Eta 6k), from contour data with the AGCM CPTEC utilizing the parameterization Berger (1978). The results were compared with simulations of other models and paleoclimate indicators, to understand how much the Eta model is able to simulate changes in the SA climate during the MH. The results of the experiment (Eta 6k) suggest climate is found on the wetter northeast Brazil during the HM, agreeing with results proxy. A decrease in the convergence of winds from the Amazon basin for southeastern Brazil influenced formation positioning South Atlantic Convergence Zone (SACZ), resulting in a possible reduction in the transport of moisture causing a reduction in rainfall in the Southeast, Midwest and southern Brazil, in agreement with results proxy. Studies reported a decrease in temperature for the HM was found on the Northeast, Midwest, Southeast and South of Brazil. Amazon basin was slightly warmer and other transition regions showed no change of weather, these results are in agreement with proxy records.